Prevention of deep venous thrombosis in stroke: a best practice implementation project. Issue 3 (9th September 2021) - Luo, Yansi; Zhou, Chunlan; Deng, Qiulin; Xu, Weihao; Zhang, Xiaomei
ABSTRACT: Objectives: The current evidence implementation project aims to promote evidence-based practice in the care of patients with stroke, specifically around the prevention of deep venous thrombosis (DVT), in the neurology department of a tertiary hospital in Guangzhou, China. Introduction: The prevalence of DVT within 14 days after stroke is 10–75%. Approximately 20% of patients with DVT develop pulmonary embolism, the third most common cause of death in patients with stroke and the most common cause of autopsy-verified death between the second and fourth week after stroke. Several risk factors are associated with the development of DVT, many of which can be alleviated by evidence-based strategies that can prevent or reduce the risk of DVT. Methods: The current evidence implementation project utilized the Joanna Briggs Institute Practical Application of Clinical Evidence System program and involved 30 patients in each audit criterion. Interventions included staff education, involvement of rehabilitation staff, and building a patient education bundle. A postimplementation reaudit was undertaken including the same number of patient samples. Results: The baseline audit results showed that the compliances for two audit criteria (patient mobilization and patient education) were under 20%, whereas those for the other criteria were at least 60%. After implementing the strategies, there were significant improvements especially in the two weak-compliance criteria. In addition, the overall compliance for most criteria increased. Conclusion: The project standardized the DVT prevention process in the Neurology Department of Nanfang Hospital. The overall compliance with DVT prevention for patients with stroke in the department improved.